2022
DOI: 10.1186/s41235-022-00400-x
|View full text |Cite
|
Sign up to set email alerts
|

The effects of face coverings, own-ethnicity biases, and attitudes on emotion recognition

Abstract: As a result of the COVID-19 pandemic, face coverings were introduced as a safety measure in certain environments in England and some research suggests that they can affect emotion recognition. Factors such as own-ethnicity bias (e.g. whether people perceiving and expressing emotions are of the same ethnicity) and social biases are also known to influence emotion recognition. However, it is unclear whether these factors interact with face coverings to affect emotion recognition. Therefore, this study examined t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
6
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 62 publications
2
6
0
1
Order By: Relevance
“…First, analysis of ratings on Scales 2, 3 and 4 revealed that faces expressing sadness were perceived of more as expressing sadness (Scales 2 and 3) or as being more negative (Scale 4) in the unmasked condition than in the pink and red mask conditions for Scale 3, and whatever the color of the mask for Scales 2 and 4. This particular sensitivity of sadness recognition to the presence of a mask is congruent with some previous studies suggesting a particular decrease in sad face recognition with a mask 19 , 20 , 22 , 26 . More specifically, after disgust (not used in the present study), sadness appears to have been the expression most impacted in several studies performed in adults 20 , 22 .…”
Section: Discussionsupporting
confidence: 91%
See 3 more Smart Citations
“…First, analysis of ratings on Scales 2, 3 and 4 revealed that faces expressing sadness were perceived of more as expressing sadness (Scales 2 and 3) or as being more negative (Scale 4) in the unmasked condition than in the pink and red mask conditions for Scale 3, and whatever the color of the mask for Scales 2 and 4. This particular sensitivity of sadness recognition to the presence of a mask is congruent with some previous studies suggesting a particular decrease in sad face recognition with a mask 19 , 20 , 22 , 26 . More specifically, after disgust (not used in the present study), sadness appears to have been the expression most impacted in several studies performed in adults 20 , 22 .…”
Section: Discussionsupporting
confidence: 91%
“…This particular sensitivity of sadness recognition to the presence of a mask is congruent with some previous studies suggesting a particular decrease in sad face recognition with a mask 19 , 20 , 22 , 26 . More specifically, after disgust (not used in the present study), sadness appears to have been the expression most impacted in several studies performed in adults 20 , 22 . However, this result is to be contrasted with those reported by Ruba and Pollak (2020) 25 or obtained before the mask issue arose 64 , which suggest that sad expressions are better processed by focusing on the upper part of the face.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…a face mask on social interactions was found to also alter facial emotion recognition (Carbon, 2020;Bani et al, 2021;Grundmann et al, 2021;Noyes et al, 2021;Cooper et al, 2022;Ramachandra and Longacre, 2022), in adults as in young children (Gori et al, 2021). However, in all these studies the effect of individual characteristics on the regulation of social spaces when interacting with people wearing a face mask was not taken into account.…”
Section: Introductionmentioning
confidence: 97%